IMPLEMENTASI METODE BERCERITA MENGGUNAKAN CERITA DALAM MENGEMBANGKAN BAHASA RESEPTIF ANAK USIA 5-6 TAHUN DI TK ISLMIC CENTER SAMARINDA - Yomi Rohmah, Siti; Liana, Heppy; Hidayah, Lailatul (Universitas Nahdlatul Ulama Kalimantan Timur, 2023)
Language skills in receptive children have been developed from an early through various methods of learning by telling stories. This study aimed to determine the implementation of telling stories methods using the story of Uut & Uti as well as the development of the language-receptive children aged 5-6 years in the kindergarten Islamic Center Samarinda. This research was qualitative research with the subject of research being six students aged 5-6 years in the level of kindergartens. Collecting data was carried out using observation, interview, and documentation. The Analysis technique used Milles and Huberman's analysis. The result was delivered by using the props. The steps of this result were to set children's preparation in receiving the story, set a seat position of children, tell the introduction of the story and the characters in the story, and deliver the contents using children's language clearly and fluently, at the end of the story, the teacher asked questions. The result shows that the ability of receptive language in the range of 5-6 years improved well in giving attention, understanding the command and the contents of the story then also retelling the story.